TRUST: THE CONNECTING LINK BETWEEN ORGANIZATIONAL THEORY AND PHILOSOPHICAL ETHICS - Hosmer, LaRue Tone (Academy of Management Review, 1995)
Numerous researchers have proposed that trust is essential for understanding interpersonal and group behavior, managerial effectiveness, economic exchange and social or political stability, yet according to a majority of these scholars, this concept has never been precisely defined. This article reviews definitions from various approaches within organizational theory, examines the consistencies and differences, and proposes that trust is based upon an underlying assumption of an implicit moral duty. This moral duty—an anomaly in much of organizational theory—has made a precise definition problematic. Trust also is examined from philosophical ethics, and a synthesis of the organizational and philosophical definitions that emphasizes an explicit sense of moral duty and is based upon accepted ethical principles of analysis is proposed. This new definition has the potential to combine research from the two fields of study in important areas of inquiry.